Structure beyond pair correlations: X‐ray cross‐correlation from colloidal crystals. Issue 6 (8th November 2016) - Lehmkühler, Felix; Fischer, Birgit; Müller, Leonard; Ruta, Beatrice; Grübel, Gerhard
Abstract : An X‐ray cross‐correlation study with emphasis on colloidal crystals is presented and demonstrates how to access higher‐order structure beyond pair correlations. In this way symmetries of the crystal can be determined that are inaccessible in conventional crystallography. Abstract : The results of an X‐ray cross‐correlation analysis (XCCA) study on hard‐sphere colloidal crystals and glasses are presented. The article shows that cross‐correlation functions can be used to extract structural information beyond the static structure factor in such systems. In particular, the powder average can be overcome by accessing the crystals' unit‐cell structure. In this case, the results suggest that the crystal is of face‐centered cubic type. It is demonstrated that XCCA is a valuable tool for X‐ray crystallography, in particular for studies on colloidal systems. These are typically characterized by a rather poor crystalline quality due to size polydispersity and limitations in experimental resolution because of the small q values probed. Furthermore, nontrivial correlations are observed that allow a more detailed insight into crystal structures beyond conventional crystallography, especially to extend knowledge in structure formation processes and phase transitions.